2022
DOI: 10.3389/fcvm.2021.805812
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Gut Microbiome and Serum Metabolome in Coronary Artery Disease Patients Complicated With Non-alcoholic Fatty Liver Disease Are Associated With Adverse Cardiovascular Outcomes

Abstract: Rationale: Patients suffering from coronary artery disease (CAD) complicated with nonalcoholic fatty liver disease (NAFLD) present worse cardiovascular outcomes than CAD patients without NAFLD. The progression of CAD is recently reported to be associated with gut microbiota and microbe-derived metabolites. However, it remains unclear how the complication of NAFLD will affect gut microbiota and microbe-derived metabolites in CAD patients, and whether or not this interplay is related to the worse cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 79 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Moreover, studies have shown that the LPS of E. coli can penetrate cardiac tissues and reach blood circulation, which leads to a thrombogenic effect (Carnevale et al 2020). E. coli, along with Dialister invisus, has been linked with periodontal abscess, periodontitis, caries, halitosis, apical periodontitis-infected pulpal tissues, and decayed teeth (Tandon et al 2013;Hu et al 2022). This strengthens the relationship between these oral diseases and CVDs, which has been proven by various studies (Sanz et al 2020;Kim et al 2019).…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, studies have shown that the LPS of E. coli can penetrate cardiac tissues and reach blood circulation, which leads to a thrombogenic effect (Carnevale et al 2020). E. coli, along with Dialister invisus, has been linked with periodontal abscess, periodontitis, caries, halitosis, apical periodontitis-infected pulpal tissues, and decayed teeth (Tandon et al 2013;Hu et al 2022). This strengthens the relationship between these oral diseases and CVDs, which has been proven by various studies (Sanz et al 2020;Kim et al 2019).…”
Section: Discussionmentioning
confidence: 83%
“…Contrary to our results, P excrementihominis is reduced in patients with either alcohol-associated hepatitis 52 or cardiovascular disease complicated with nonalcoholic fatty liver disease, positioning this species as potentially protective. 53 However, another recent study demonstrated P excrementihominis was induced significantly in patients with irritable bowel syndrome and may be associated with intestinal inflammation. 21 Our data indicate significantly increased inflammatory gene expression in liver, ileum, and colon, which could be mediated by changes in the gut microbiome and increased circulating LPS ( Figure 6 A ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study of 132 participants showed that the gut microbiome of individuals with coronary artery disease coexisting with NAFLD was characterized by increased abundance of Dialister compared with healthy volunteers. 38 Interestingly, a case-control study of Chinese urban adults showed that the relative abundance of Dialister was higher in NAFLD subjects compared with healthy participants, and it was higher in males compared with female NAFLD subjects. 39 The above-mentioned results have demonstrated that fish oil plus vitamin D 3 has respectable efficacy in the treatment of NAFLD by regulating the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%